Trade Policy and Poverty Reduction in Brazil - Harrison, Glenn W.; Rutherford, Thomas F.; Tarr, David G.; Gurgel, Angelo (Washington, DC: World Bank, 2014)
A multi-region computable general equilibrium model is used to evaluate the regional, multilateral, and unilateral trade policy options of Mercosur from the perspective of the welfare of all potential partners in several proposed agreements. The focus for Brazil is on poverty impacts. The results show that the poorest households in Brazil experience gains of 1.5-5.5 percent of their consumption, which are about three to four times the average gains for Brazil. Protection in Brazil favors capital-intensive manufacturing relative to unskilled labor-intensive agriculture and manufacturing. So trade liberalization raises the return to unskilled labor relative to capital and disproportionately helps the poor.